Efeitos da redução da concentração de sódio na solução de hemodiálise e no conteúdo de sódio da dieta sobre a resposta inflamatória de pacientes com doença renal crônica - Telini, Lidiane Silva Rodrigues [UNESP] (2014)
The prognosis of chronic kidney disease patients is strongly influenced by cardiovascular complications. Inflammation is known to be one of the risk factors for these complications, occurring in about 30% of dialysis patients. Increasing evidences have suggested that the volume overload is one of the causes of inflammation in these patients. In a previous study in our center, we found that reducing the sodium content (Na) in the diet and in dialysis solution were associated with reduced concentrations of inflammatory markers in patients on hemodialysis (HD). However, in both studies a reduction in markers of body water volume was not found. These results could be due to the low sensitivity of the volume markers used or suggest a direct role of Na as an inflammatory inducer independent of the volume. The present study aims to confirm the hypothesis that the mobilization of sodium reduces the body water volume and attenuates the inflammatory state in HD patients, using a more sensitive volume marker as the type B atrial - natriuretic peptide (BNP). Ninety-eighty patients were included and randomly allocated into three groups: diet, treated with reduction of 2 g/day of dietary Na intake; dialysate, exposed to reduction of dialysate Na concentration from 138 to 135 mEq/L, and control group. The patients were followed up for 16 weeks. The baseline characteristics were similar among the groups. Clinical data, such as blood pressure, interdialytic weight gain; medications prescription, hypotension and cramps did not vary significantly among the groups. Serum concentrations of biochemical markers showed no significant changes among the groups, except for transferrin saturation, which showed an increase at week 8 comparing to initial evaluation in the diet group. Hematological markers did not change in diet and control groups, but in the dialysate group, a significant increase in hematocrit and hemoglobin levels were observed in the follow ...